Analisis Peran Sektor Pertanian dan Sektor Industri terhadap Kesejahteraan Masyarakat Melalui Pertumbuhan Ekonomi PDRB di Provinsi Banten - Moch Faisal; Achmad Tjachja Nugraha; Iwan Aminudin (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
The role of the agricultural and industrial sectors on community welfare through the economic growth of GRDP in Banten Province. This study intends to examine the state of economic growth in Banten Province, analyzing the role of the agricultural sector and the industrial sector on economic growth and community welfare. This data was obtained from the Central Bureau of Statistics of Banten Province in 2001-2021. The analysis method used is path analysis using SPSS for Windows version 16. The results showed that the direct role of the agricultural sector, the industrial sector and the economic organization of GRDP played an insignificant role in the welfare of the people of Banten Province, while the indirect role of the industrial sector had a positive and significant effect on the economic growth of GRDP in Banten Province.